Progression of planovalgus deformity in patients with cerebral palsy - Min, Jae Jung; Kwon, Soon Sun; Sung, Ki Hyuk; Lee, Kyoung Min; Chung, Chin Youb; Park, Moon Seok (BMC Musculoskeletal Disorders, 2020)
Background: Analyzing radiographic changes of pes planovalgus(PV) deformity of cerebral palsy(CP) patients according to age and influencing factors. Methods: CP patients with PV deformity younger than 18 years old who had undergone more than a year of follow-up with at least two standing foot radiographs were included. Anteroposterior and lateral talo-first metatarsal(talo-1stMT), talo-second metatarsal(talo-2ndMT), and hallux valgus(HV) angles were measured on the radiographs. The rate of progression was adjusted by multiple factors using the linear mixed model, with the Gross Motor Function Classification System(GMFCS) level as the fixed effect and age and each subject as random effects. Results: Overall, 194 patients were enrolled in this study, and 1272 standing foot radiographs were evaluated. The AP talo-2ndMT angle progressed by 0.59° (p < 0.0001) and 0.64° (p = 0.0007) in GMFCS level II and III patients, respectively; however, there was no significant change in GMFCS level I patients (p = 0.3269). HV was significantly affected by age in all three GMFCS groups; it increased by 0.48° (p < 0.0001), 0.66° (p < 0.0001), and 1.19° (p < 0.0001) for levels I, II, and III, respectively. The lateral talo-1stMT angle showed improvements in GMFCS level I and II patients (0.43°, p < 0.0001, and 0.61°, p < 0.0001, respectively). In GMFCS level III patients, there was no significant improvement in the lateral talo-1stMT angle (p = 0.0535). Conclusions: The GMFCS level was the single most important factor influencing the progression of radiographic indices in PV deformity in CP. The AP talo-1stMT and talo-2ndMT angles progressed in patients with GMFCS levels II and III. Physicians should take this result into consideration when planning the timing of the surgery. Level of evidence: Prognostic Level IV.
Keywords: Adolescent; Cerebral Palsy; Child; Child, Preschool; Disease Progression; Female; Flatfoot; Follow-Up Studies; Humans; Male; Retrospective Studies; Cerebral palsy; Pes planovalgus; Progression; Talo-first metatarsal angle; Talo-second metatarsal angle